A three-level aggregation model for evaluating software usability by fuzzy logic - Rakovská, Eva; Hudec, Miroslav (Zielona Góra: Uniwersytet Zielonogórski)
Rapid deployment of IT brings about new issues with software usability measurement. Usability is based on users? experience and is strongly subjective, having a qualitative character. The users` comfort is usually collected by surveys in their daily work. The present article stems from an experimental study related to the evaluation of the usability of tools by a rule-based system.
Keywords: measuring software usability; rule-based systems; fuzzy quantifiers; aggregation functions; questionnaire